Girl with a pearl earring [videorecording (DVD)] - Webber, G. P. (G. Peter); Firth, Colin, 1960-; Johansson, Scarlett, 1984-; Wilkinson, Tom, 1948-; Chevalier, Tracy (Lions Gate Home Entertainment, 2004)
17-year-old Griet must work to support her family, so she becomes a maid in the house of Johannes Vermeer, where she attracts the master painter's attention. He is commissioned to paint Griet, and the result is one of the greatest paintings ever created.